Evaluación del potencial térmico solar para la generación de energía eléctrica en la empresa Wartsila Ecuador, ubicada en el sector de Tababela - Quito. Diseño de un sistema fotovoltaico complementario a la red eléctrica. - Zambrano Jiménez, Ángel Fernando (2017)
This study involves the design of a photovoltaic installation connected to the grid for a private company in Tababela - Quito. The design is based on both, environmental and technical benefits that are assigned through the integration of this technology with the Ecuadorian energy matrix. The average monthly consumption of the company and the solar irradiation in Tababela were taken into account as a fundamental part of the system design. In order to obtain the electricity consumption, an electrical grid analyzer and the database of electricity consumer bills during a year were used to obtain a better view of load behavior in the company and with them sizing the photovoltaic system. For the estimation of the solar potential in the place, an analysis was made taking data about the solar radiation from January to May, it was compared with other available sources such as NASA, ‘Atlas solar del Ecuador’ and meteorological stations of the Environment Secretary, specifically Tumbaco Station that is located 8 Km from the company. The sizing of the photovoltaic installation was made considering technical specifications and meteorological characteristics that affect the system, obtaining a photovoltaic system of three-phase injection to the electrical grid, with 9600 Wp power. The monthly solar irradiance average values obtained (5kWh / m2 / day approximately) in Tababela sector, an annual generation of 15848.63 kWh was obtained. It allows us to determine an annual performance average of 1650.89 kWh / kWp for this area. Annually this clean and decentralized generation would contribute to reduce 11.88 tons of CO2 approximately, generated by the fuel-oil combustion (diesel oil) to produce this amount of energy, this can be considered as an environmental benefit that contributes to reduce the emission of greenhouse gases. In addition, it is guaranteed that the production of the company is not affected in case of a higher demand than the one generated or a failure in the photovoltaic system because of its characteristic of being connected to the national electrical grid.